Determining Evaluation Criteria And Sub-Criteria For E-Learning Software - Saad, Ahmad Fadli; Abdullah, Rukaini; Shuib, Liyana (Malaysian Journal of Computer Science, 2017)
Today’s demands for e-learning have led to the emergence of numerous and diverse e-Learning software (e-LS) products in the market. With such a myriad of choices, selecting an e-LS can be difficult. In any software evaluation process, evaluation criteria are important for correct selection to be made. However, in the case of e-LS selection, information about its evaluation criteria is lacking. Hence, a Delphi study was conducted to identify the evaluation criteria for e-LS. This paper presents the study and its results. Eleven criteria and sixty six 66 sub-criteria were identified from the literature. A questionnaire comprising the criteria as items was distributed to 31 experts in the first round. 16 sub-criteria were added by the experts. After two Delphi rounds, three criteria were considered as being extremely important and eight criteria as important. One sub-criteria was rejected as it did not achieve the majority of expert consensus. In total, 11 criteria and 81 sub-criteria were obtained from this study. The results of this study indicate that these criteria and sub-criteria are important in the evaluation of e-LS.